Thermodynamic Optimization and Exergy-Based Performance Analysis of Hybrid Thermal Management Systems for Electric Vehicles - Anushka Mukharjee (International Journal of Energy and Thermal Applications, 2025)
The transition toward sustainable transportation has brought electric vehicles (EVs) to the forefront of modern engineering innovation. Despite their environmental benefits and improved energy efficiency, EVs face major thermal challenges that affect performance, safety, and durability. Efficient thermal management of batteries, power electronics, and electric drive systems is vital to ensure reliability under diverse operating conditions. This study presents a detailed thermodynamic optimization and exergy-based performance analysis of hybrid thermal management systems (HTMS) for electric vehicles. The hybrid approach combines liquid cooling, air convection, phase change materials (PCMs), and thermoelectric modules to enhance heat dissipation, minimize exergy losses, and improve system efficiency. The thermodynamic analysis follows both the first and second laws, enabling the evaluation of energy flow and irreversibilities. Exergy analysis reveals that heat exchangers and coolant loops are the dominant contributors to exergy destruction, accounting for approximately 60% of total system losses. The study employs numerical simulation and parametric optimization methods to evaluate the influence of coolant flow rate, PCM melting point, and thermoelectric module power on performance. Results indicate that optimized hybrid systems achieve 25–40% improvement in temperature uniformity and 15–20% enhancement in exergy efficiency compared to conventional liquid cooling. Moreover, waste heat recovery through thermoelectric generation provides additional energy gains, improving EV range by 5–8%. The research highlights the potential of exergy-guided design frameworks for developing high-performance, sustainable thermal systems. The integration of advanced materials, intelligent control algorithms, and data-driven predictive models can further improve thermal adaptability under dynamic driving conditions. The outcomes of this work establish the hybrid thermodynamic optimization approach as a promising pathway for next-generation electric vehicle thermal management, ensuring better energy utilization, extended component lifespan, and reduced environmental impact.
Keywords: Exergy Analysis; Hybrid Thermal Management System; Sustainability; Thermodynamic Optimization; Waste heat recovery; battery thermal management; electric vehicles; energy efficiency; phase change materials (PCMs); thermoelectric cooling